Prawne aspekty informatyzacji w świetle uregulowań ustawy z 6.8.2010 r. o dowodach osobistych - Tomaszewska, Katarzyna (Kwartalnik Prawa Publicznego, 2015)
Identity cards are a basic example of documentation which every Polish citizen who reached the age of majority must possess and use. Identity cards fulfil a double function. On the one hand they are fundamental in determining identity and confirming Polish citizenship. On the other hand these are documents which authorize to cross country borders. Their meaning as official documents is not doubtful nowadays and it is obvious that it is necessary to facilitate the recent procedure for the issuance and registration of these documents. This concerns applying solutions appropriate for the computerization process. Its elements are provided for in the Act of 6th of August 2010 on identity cards. Such solutions have been outlined and discussed in the considerations included in this study.